Effects Of Chemical Cues On The Larval Settlement, Metamorphosis And Mortality Rate Of Two Species Of Tropical Oysters (Crassostrea Iredalei And Crassostrea Belcheri) - Teh, Chiew Peng (2013)
Larvae settlement and metamorphosis were important for the cultivation of tropical inoysters in Malaysia. Inducing greater degree of larval settlement and metamorphosis of commercial oysters using neuroactive compounds can significantly improved the seed production in hatcheries for these valuable species. Although these oysters are cultivated in Malaysia, the market demand was higher compared to the production. For this purpose, this study was aimed at the laboratory assessment of the larval settlement and metamorphosis of two tropical oysters, Cupped oyster (Crassostrea belcheri) and Slipper oyster (C. iredalei) using four different neuroactive compounds, namely epinephrine (EPI), L-3,4-dihydroxyphenylalnine (L-DOPA), norepinephrine (NE) and serotonin (5-HT) at five different concentrations (10-3, 10-4, 10-5,10-6 and 10-7 M) for 1 h and 24 h exposure time. Larvae from different broodstock showed different efficiency toward different neuroactive compounds. This results show that NE at 10-7 M yielded the highest larval settlement and metamorphosis of C. belcheri larvae with 290 μm shell length (SL) (11 folds at 10-7 M compared with control). 10-7 M 5-HT managed to induce two folds of larval settlement and metamorphosis of C. belcheri 300 μm SL.